2018
DOI: 10.1111/jocn.14340
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and attitudes on the relationship between spirituality, religiosity and health: A comparison between nursing students from Brazil and Portugal

Abstract: These findings could contribute to raise awareness on the importance of improving the training of relational competencies that prepare students to address the dimension of spirituality and religiosity with their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
12
0
3
Order By: Relevance
“…The results of different studies[1718192021222324383940] indicated the role of self-blaming, ruminating, and catastrophic appraisal in the development of anxiety. Several investigations were also conducted in this field in Iran[91017182932] and reported similar results. In explaining the effect of cognitive emotional regulation strategies on affection and anxiety, it can be concluded that since cognition, affection, and behavior are in close interaction with each other, the cognitive emotion regulation can change the function of cognitive systems (including memory, attention, and consciousness) by controlling the attention and cognitive outcomes of emotion and then regulate the emotion.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results of different studies[1718192021222324383940] indicated the role of self-blaming, ruminating, and catastrophic appraisal in the development of anxiety. Several investigations were also conducted in this field in Iran[91017182932] and reported similar results. In explaining the effect of cognitive emotional regulation strategies on affection and anxiety, it can be concluded that since cognition, affection, and behavior are in close interaction with each other, the cognitive emotion regulation can change the function of cognitive systems (including memory, attention, and consciousness) by controlling the attention and cognitive outcomes of emotion and then regulate the emotion.…”
Section: Discussionsupporting
confidence: 53%
“…[3031] People who focus on positive activities and experiences after being exposed to problems, emphasize on the productivity of convenient events and try to downgrade the seriousness and importance of such events, usually have more positive emotional adjustments with better sleep quality. [32] In the current study, a significant relationship was observed between mental health (depression, anxiety, and stress) and willpower and quality of sleep in the medical students ( P < 0.05). Ford et al ,[27] in a study showed a significant relationship between poor sleep quality and depression.…”
Section: Discussionmentioning
confidence: 56%
“…[25][26][27][28][29] Interestingly, some studies among nursing students also concluded there was a need for improvement in competencies regarding the spiritual aspects of health care. [27][28]30 In a prospective, multi-site study involving 2,193 nursing and midwifery students, Ross and colleagues found that a broad view of what encompasses spirituality and high personal engagement in spirituality appears to correlate best with self-perceived competence in providing spiritual care to patients. 31 Similarly, Damiano and colleagues evaluated 106 medical students in the United States and found that spiritual openness was predictive of empathy scores.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by Cordero et al from Seville, Spain, examined 75 graduate students (nurses, podiatrists and physiotherapists) using the RSMPP and the DUREL index in 2017, 22 and the same research group also examined Portuguese nursing students in 2016 using the same questionnaires. 23 In addition, Menegatti-Chequini et al in performed two surveys of psychiatrists in 2013-2014, a local facility sample in São Paulo (N = 84), and a nation-wide sample among members of the Brazilian Psychiatric Association (N=508) using a questionnaire based on the RSMPP. 24,25 Details of the citation search hits are found in Table 2.…”
Section: Systematic Searchesmentioning
confidence: 99%